The Condition of Electricity Oversupply in Indonesia - Redaputri, Appin Purisky (Journal of Earth Energy Engineering, 2023)
The purpose of this study is to determine the condition of electricity supply in Indonesia, which experienced a shortage in 2015 but is currently experiencing an oversupply. Starting from the existence of a 35,000 MW mega project which turned out to be in line with the Covid-19 pandemic, the use of electrical energy was stagnant, even though the addition of electrical energy supply continued to grow. This is also coupled with the problem of the proportion of fossil energy use which is still more than that of new and renewable energy. So that makes PLN have to spend a large amount of money and has not been balanced with the results obtained. The solution is to increase electricity demand, namely by adding new market niches to increase productive electricity demand. As well as through various bundling and promos to increase customer comfort, for example, promos to increase power, discount home charging for electric vehicle owners, the use of electric stoves and so on.